Growth performance, immune response, and resistance of Nile tilapia fed paraprobiotic Bacillus sp. NP5 against Streptococcus agalactiae infection - Aldy Mulyadin; Widanarni, Widanarni; Yuhana, Munti; Wahjuningrum, Dinamella (Indonesian Society of Scientific Aquaculture (ISSA), 2021)
ABSTRACT This study was aimed to evaluate the effectiveness of Bacillus sp. NP5 paraprobiotic administration through commercial feed on growth performance, immune response, and resistance of Nile tilapia against Streptococcus agalactiae infection. Bacillus sp. NP5 paraprobiotic was produced through heat-inactivation at 95°C for 1 h, then performed a viability test on tryptic soy agar (TSA) media and incubated for 24 hours. Paraprobiotics could be used whether the bacteria did not grow on the TSA media. This study used a completely randomized design, containing three treatments with five replications, i.e. 1% (v/w) probiotic addition, 1% (v/w) paraprobiotic addition, and no addition of probiotic or paraprobiotic (control). The experimental fish were reared for 30 days. On day 31 of rearing, fish were challenged with S. agalactiae (107 CFU/mL) through intraperitoneal injection route, while the negative control was injected with PBS. This study results significantly improved growth performances and immune responses (P<0.05), compared to control after 30 days of probiotic and paraprobiotic Bacillus sp. NP5 administration. After challenge test, increased immune responses in probiotic and paraprobiotic of Bacillus sp. NP5 treatment had higher survival rates (P<0.05) than positive control. The administration of Bacillus sp. NP5 probiotic and paraprobiotic through commercial feed were effective in increasing growth performance, immune response, and resistance of Nile tilapia against S. agalactiae infection. Keywords: Bacillus sp. NP5, Nile tilapia, paraprobiotic, Streptococcus agalactiae ABSTRAK Penelitian ini bertujuan mengevaluasi efektivitas pemberian paraprobiotik Bacillus sp. NP5 melalui pakan dalam meningkatkan kinerja pertumbuhan, respons imun, dan resistansi ikan nila terhadap infeksi Streptococcus agalactiae. Proses pembuatan bakteri paraprobiotik yaitu Bacillus sp. NP5 diinaktivasi panas pada suhu 95°C selama 1 jam, dilanjutkan dengan pengujian viabilitas dengan menyebarkannya pada media tryptic soy agar kemudian diinkubasi selama 24 jam. Jika bakteri tidak tumbuh, maka paraprobiotik dapat digunakan. Penelitian ini menggunakan rancangan acak lengkap dengan tiga perlakuan dan lima ulangan, yaitu penambahan probiotik 1% (v/w), penambahan paraprobiotik 1% (v/w), dan tanpa penambahan probiotik atau paraprobiotik (kontrol). Ikan perlakuan dipelihara selama 30 hari dan pada hari ke-31, ikan diuji tantang dengan S. agalactiae (107 CFU/mL) melalui injeksi intraperitoneal, sementara perlakuan kontrol negatif diinjeksi dengan PBS. Hasil penelitian setelah 30 hari pemberian probiotik dan paraprobiotik Bacillus sp. NP5 menunjukkan kinerja pertumbuhan dan respons imun yang meningkat signifikan (P<0.05) dibandingkan dengan kontrol. Pascauji tantang, peningkatan respons imun pada perlakuan probiotik dan paraprobiotik Bacillus sp. NP5 menunjukkan tingkat kelangsungan hidup yang lebih tinggi (P<0.05) dibandingkan kontrol positif. Pemberian probiotik dan paraprobiotik Bacillus sp. NP5 melalui pakan dapat meningkatkan kinerja pertumbuhan, respons imun, dan resistansi ikan nila terhadap infeksi Streptococcus agalactiae. Kata kunci: Bacillus sp. NP5, ikan nila, paraprobiotik, Streptococcus agalactiae